No Change in Social Decision-Making Following Transcranial Direct Current Stimulation of the Right Temporoparietal Junction - Blair-West, Laura F. (Front Neurosci, 2018)
The right temporoparietal junction (rTPJ) is thought to play an important role in social cognition and pro-social decision-making. One way to explore this link is through the use of transcranial direct current stimulation (tDCS), a non-invasive brain stimulation method that is able to modulate cortical activity. The aim of this research was therefore to determine whether anodal tDCS to the rTPJ altered response to a social decision-making task. In this study, 34 healthy volunteers participated in a single-center, double-blinded, sham-controlled crossover design. Subjects received 20 min of active/sham anodal tDCS to the rTPJ before undertaking the Ultimatum Game (UG), a neuroeconomics paradigm in which participants are forced to choose between monetary reward and punishing an opponent's unfairness. Contrary to expectations, we found no significant difference between anodal and sham stimulation with regard to either the total number or reaction time of unfair offer rejections in the UG. This study draws attention to methodological issues in tDCS studies of the rTPJ, and highlights the complexity of social decision-making in the UG.